Enhancement of Chemokine mRNA Expression by Toll-Like Receptor 2 Stimulation in Human Peripheral Blood Mononuclear Cells of Patients with Atopic Dermatitis. (21st March 2020) - Yu, Yangyang; Lin, Dongxu; Cai, Xiaoqiong; Cui, Danni; Fang, Ran; Zhang, Wei; Yu, Bo; Wang, Xiaomei
Abstract : Atopic dermatitis (AD) is a chronic inflammatory skin disease which is often associated with Staphylococcus aureus ( S. aureus ) colonization. S. aureus ingredients are potential ligands to activate the Toll-like receptor 2 (TLR2) and drive inflammatory cytokine or chemokine production. However, the role of TLR2-mediated chemokine expression in AD development has not been systematically investigated. In this study, we sought to determine the mode of TLR2-mediated chemokine expression in AD patients. Human peripheral blood mononuclear cells (PBMCs) were isolated from AD patients and healthy controls. Upon incubation with TLR2 ligands Pam3CSK4 and PGN, mRNA expression of chemokines, including CCL1, CCL5, CCL8, CCL13, CCL17, CCL18, CCL22, and CCL27, were determined by quantitative real-time polymerase chain reaction (qRT-PCR) analysis. The results showed that basal mRNA expression of CCL17 in PBMCs from AD patients was upregulated compared with healthy controls, while those of CCL8 and CCL13 were downregulated. When stimulated with TLR2 ligands, the mRNA expression of CCL5, CCL8, CCL13, CCL18, and CCL22 in PBMCs from AD patients was significantly higher than those from healthy controls. The different basal chemokine mRNA expression profiles indicate the different immune status in patients with AD compared with healthy controls. Excessive chemokine mRNA expression induced by TLR2 activation is associated with the development of AD.